Cyclic redundancy encoder for error detection in communication channels - Khalifa, Othman Omran; Islam, Md. Rafiqul; Khan, Sheroz (2004)
Cyclic Redundancy Check is one of the most powerful methods of error detection in blocks for digital communications signals. I t involves a division of the transmined message block by a constant called the generator polynomial. The quotient is discarded, and the remainder is transmitted as the Block check Character or Frame Check Sequence. The receiving station performs the same computation on the received message block. The computed remainder, FCS is compared to the remainder received from the transmitter. If the two match, no errors have been detected in the message block. If the two do not match, either a request for retransmission is made by the receiver or the errors are corrected through use of special coding technique. This paper describes the methodology used and the implementation of the Cyclic Redundancy Check (CRC) algorithm using Ci+ programming. The technique gained its popularity because it combines three advantages: Extreme error detection capabilities, little overhead and ease of implementation. The CRC is calculated by performing a modulo 2 division of the data by a generator polynomial and recording the remainder atler division. The mnst commonly used polynomials are implemented. The conclusions and analysis results were shown and presents that the Cyclic Redundancy Check Encoder is used i n error detection for digital signals due to the ability to quickly determine if errors are present. The redundancy bits produced by the cyclic encoder enable the receiver to quickly determine if an error was produced and different types of polynomials are used i n CRC.